Carbonic anhydrase: Its biocatalytic mechanisms and functional properties for efficient CO2 capture process development. Issue 5 (10th September 2013) - Kanth, Bashistha Kumar; Lee, Jinwon; Pack, Seung Pil
<x xml:space="preserve">Abstract</x> The accumulation of carbon dioxide (CO2) is the main cause of global climate change and it is very important to develop technologies that can reduce atmospheric CO2 level. Although several physical or chemical CO2 capture processes are being developed, the efficiency of capture/sequestrationshould be increased. Carbonic anhydrase (CA, EC 4.2.1.1), a metalloenzyme, has been considered as an important biocatalyst for CO2 capture system development because CA has the highest efficiency of CO2 conversion via hydration (CO2 + H2O ↔ HCO3− + H+, kcat: ∼106 s−1). In this review, biocatalytic mechanism and functional properties of CA are reviewed in terms of its distinctive CO2 converting ability. In addition, recent applications of several CAs are presented in CO2 capture process development. This review would present guidelines for scientists and researchers to understand CA functions and develop interest in the practical applications of CA, in particular, as biocatalytic agent for more efficient CO2 capture process development.